Pain and Its Impact on the Quality of Life in Children with Hip Dislocation in Cerebral Palsy (Herald of the National Children's Medical Center, 2025)
Cerebral palsy (CP) is a leading cause of severe motor impairments in children, with progressive displacement of the hip joint resulting in subluxation or complete dislocation being a common orthopedic complication. In patients with high levels on the Gross Motor Function Classification System (GMFCS), the risk of dislocation may reach up to 90%. The main pathogenetic mechanism is a pronounced muscle imbalance, leading to lateralization of the femoral head and disruption of joint congruence. Alongside limited mobility, one of the most significant problems is severe pain syndrome, which critically impacts the quality of life of both patients and their families.
Keywords: Cerebral palsy; hip dislocation; pain syndrome; quality of life; orthopedic correction; osteotomy; Barthel Index